2010
DOI: 10.1375/prp.4.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Sudanese Perspectives on Resettlement in Australia

Abstract: Resettlement programs for people from a refugee background must respond to a variety of concerns as people from diverse backgrounds and often longstanding periods of upheaval and hardship enter their new resettlement communities. Host countries approach the demands of resettlement through varying programs and policies and those differences across countries can profoundly affect the newcomers' experiences. The current study employs quantitative and qualitative methods to examine the individual and contextual fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 22 publications
(22 reference statements)
0
17
2
Order By: Relevance
“…This is in contrast with debates over refugee resettlement elsewhere in the world (Murray, 2010) and suggests a general sense of support for refugee resettlement in the United States relative to other immigration policies. The findings across the three groups suggest that refugees and other authorized immigrants are not the focal groups in ongoing immigration debates.…”
Section: Discussioncontrasting
confidence: 77%
“…This is in contrast with debates over refugee resettlement elsewhere in the world (Murray, 2010) and suggests a general sense of support for refugee resettlement in the United States relative to other immigration policies. The findings across the three groups suggest that refugees and other authorized immigrants are not the focal groups in ongoing immigration debates.…”
Section: Discussioncontrasting
confidence: 77%
“…A number of studies have attempted to capture South Sudanese migrants' experiences in pre-migration, refugee status and post-migration from different disciplinary viewpoints (Schweitzer et al, 2006;Murray, 2010;Savage & HickeyMoody, 2012;Marlowe, 2011a;Marlowe, 2011b;Shakespeare-Finch & Wickham, 2009). These studies have identified positive and negative experiences in each of these stages and also revealed the positive hope South Sudanese migrants nevertheless have of fitting into Australian society.…”
Section: Psycho-social Perspectives On Migrants' Experiencesmentioning
confidence: 99%
“…South Sudanese migrants' psychological stress is identified in homesickness, separation from families, racial discrimination, lack of understanding of the Australian legal system, inability to access basic necessities, cultural conflicts and uncertainty of jobs (Shakespeare-Finch & Wickham, 2009;Murray, 2010;Khawaja et al, 2008). Separation from families, having experienced violence, having witnessed the murder of a family member or friend, and lacking facilities to fulfil their basic needs were mentioned as pre-migration traumatic conditions affecting anxiety, depression, somatisation and post-traumatic stress disorder (Marlowe, 2010a;Marlowe & Adamson, 2011).…”
Section: Psycho-social Perspectives On Migrants' Experiencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its proponents are often accused of paying scant attention to the negative elements of social relationships such as the associated obligations and restrictions, as well as the development of behaviours and attitudes in group members that are anti-social (Tzanakis 2013). Nonetheless, Putnams work on social capital concept has been particularly useful to us because social connectedness, in its various forms, can be closely linked to feelings of wellbeing for refugees and therefore, contribute to successful resettlement (Murray, 2010).…”
Section: The Concept Of Capitalmentioning
confidence: 99%